Technical and physical match performance of teams in the 2018 FIFA World Cup: Effects of two different playing styles - Yi, Q.; Gómez, M. A.; Wang, L.; Huang, G.; Zhang, H.; Liu, H. (Journal of Sports Sciences, 2019)
In order to investigate the effect of playing styles on the match performance of football teams, data were analysed on 18 technical performance-related variables and 8 physical performance-related variables from 59 matches in the 2018 FIFA World Cup. A k-means cluster analysis was conducted to classify all match observations into two clusters of tactical approach in order to identify the playing styles of teams (characterised as direct-play, possession-play and mixed-play). Separate Poisson regression models were run in the generalised mixed linear modelling to examine the differences in technical and physical performance between teams classified as using different playing styles when facing different opponents. Results showed that possession-play characterised teams achieved higher values in all the variables related to goal scoring, attacking and passing (ES: 0.32 ~ 1.27) and covered more distance in sprints and high-intensity running (ES: 0.33 ~ 0.47) than direct-play characterised teams. Both possession- and direct-play characterised teams achieved higher values in passing, pass accuracy and delivery into the attacking third playing against direct-play characterised teams than playing against possession-play characterised sides (ES: 0.22 ~ 0.98). These findings may provide insights into the establishment of performance profiles of teams with different tactical styles and the development of specific training drills to optimise playing style.